1996
DOI: 10.1038/nbt0396-339
|View full text |Cite
|
Sign up to set email alerts
|

Virosomes: Cationic Liposomes Enhance Retroviral Transduction

Abstract: Retrovirus-derived vectors are overwhelmingly preferred over other methods for ex vivo gene therapy because they provide permanent integration of foreign genes into cellular DNA. In comparison, cationic lipids mediate efficent gene transfer, but expression is transient. When we combined cationic lipids with retrovirus particles we obtained a significant enhancement of transduction efficiency, depending upon the type of lipid formulation and the dose used. The relative effectiveness of these cytofectins was: DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 15 publications
2
60
0
1
Order By: Relevance
“…Polycationic agents such as polybrene and DEAE dextran are often used to increase the transduction efficiency in mammalian cells (Hodgson et al, 1996;Singh and Rigby, 1996). In the absence of polycationic agents, virus and cells tend to repel each other as they both have negatively charged surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Polycationic agents such as polybrene and DEAE dextran are often used to increase the transduction efficiency in mammalian cells (Hodgson et al, 1996;Singh and Rigby, 1996). In the absence of polycationic agents, virus and cells tend to repel each other as they both have negatively charged surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Polybrene (14), DEAE-dextran (15), or poloxamers (16)), cationic lipids (e.g. Lipofectin or Lipofectamine (17,18)), or cationic peptides/proteins (e.g. fibronectin fragments (19 -21), protamine sulfate (22), prostatic acid phosphatase fragments (23), or HIV-1 gp41-and gp120-derived peptides (24,25)).…”
Section: Lentiviral Vectors (Lvs)mentioning
confidence: 99%
“…Recently several authors have demonstrated in vitro that complexing virus particles with cationic amphiphiles can enhance virus infection above that observed in the presence of polybrene. [11][12][13] Such amphiphiles have been used for several years to mediate DNA transfer to cells, albeit at a lower efficiency than viruses. They include cationic liposomes which are lamellar vesicles and a variety of cationic compounds in either linear or branched form with the ability to complex negatively charged molecules.…”
Section: Introductionmentioning
confidence: 99%